Determinant factor of firm value in covid-19 pandemic: role of dividend policy as mediating variable - Gregorius Paulus Tahu; Anik Yuesti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The purpose of this research is to analyze the determinant factors of firm value during the COVID-19 pandemic and the role of dividend policy as a mediation variable. This study uses multiple linear regression and the Sobel test as a data analysis tool to measure dividend policy as a mediating variable between profitability, liquidity, free cash flow, leverage, company growth, investment opportunities, and company value during the COVID-19 pandemic. The results of the study show that profitability, liquidity, free cash flow, leverage, company growth, and COVID-19 have an effect on dividend policy and company value. However, investment opportunities have no effect on dividend policy or firm value. While the results of the Sobel test showed interaction, this study found that dividend policy mediates the effect of profitability, liquidity, free cash flow, leverage, company growth, and COVID-19 on company value. This study expands on empirical evidence on the determinants of firm value in the COVID-19 pandemic that is currently reported to be inconclusive and fills a gap in the existing literature by focusing on the issue of the determinants of firm value in the context of dividend policy as a mediating variable in the COVID-19 pandemic.